PERAN PENTING SERVICE MARKETING MIX PADA EDUCATION SERVICE - Fatik Rahayu (Universitas Trisakti, 2013)
This paper aims to examine the role of service marketing mix in education service business. A questionnaire was developed with item measurements that captures the constructs in the conceptual model. A survey of English language education business student was undertaken. The data are analyzed with multiple regression. The result show there is significant impact of service marketing mix on customer loyalty.Keywords: Service marketing mix, Loyalty, Education service